2023
DOI: 10.3389/fpls.2023.1101271
|View full text |Cite
|
Sign up to set email alerts
|

Genetic approaches to exploit landraces for improvement of Triticum turgidum ssp. durum in the age of climate change

Abstract: Addressing the challenges of climate change and durum wheat production is becoming an important driver for food and nutrition security in the Mediterranean area, where are located the major producing countries (Italy, Spain, France, Greece, Morocco, Algeria, Tunisia, Turkey, and Syria). One of the emergent strategies, to cope with durum wheat adaptation, is the exploration and exploitation of the existing genetic variability in landrace populations. In this context, this review aims to highlight the important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 217 publications
1
5
0
Order By: Relevance
“…Landraces and old wheat cultivars demonstrate remarkable genetic variation, making a valuable resource for improving modern varieties. especially in terms of quality (Broccanello et al, 2023). The ex situ and in situ landraces used in our study exhibited higher protein and wet gluten content values compared to the standard cultivars in both years, overlapped with the literature.…”
Section: Test Weightsupporting
confidence: 76%
“…Landraces and old wheat cultivars demonstrate remarkable genetic variation, making a valuable resource for improving modern varieties. especially in terms of quality (Broccanello et al, 2023). The ex situ and in situ landraces used in our study exhibited higher protein and wet gluten content values compared to the standard cultivars in both years, overlapped with the literature.…”
Section: Test Weightsupporting
confidence: 76%
“…The reason for the underutilization of landraces in breeding programs could be, among others, their tall height and late maturity [ 66 ]. However, the local landraces with high genetic diversity can serve as potential sources of new alleles for crop improvement [ 18 ]. The selection of landraces or parent lines with the best allelic combinations for local adaptation can also be facilitated by interacting with farmers’ traditional knowledge [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher genetic variation levels for the target characteristic(s) within a species imply increased opportunities to select superior genotypes from a population [ 16 ] or to have more novel traits and alleles resilient to unpredictable climate changes and new end-user demands [ 17 ]. It is vital to explore genetic variability in landrace populations in order to understand the genetic factors behind their adaptation and to identify beneficial alleles [ 18 ]. Therefore, determining the genetic diversity of Ethiopian durum wheat landraces can provide highly valuable information that will help us to broaden the genetic base of the germplasm used in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed the adaptive capacity of this material to novel conditions and its potential use in breeding programs. Therefore, landraces and indigenous varieties germplasm constitutes a valuable source for breeding resilient cultivars, focusing on adaptation traits under the rapidly changing climatic conditions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%